Compressive Strength and Acid Resistance of Fly Ash Based One-Part Geopolymer - Abdulmatin, Akkadath; Dueramae, Saofee; Benchaphong, Apai; Thongraksa, Apiwish; Pethrung, Sirichai (Civil Engineering Journal, 2026)
This research studied the properties of one-part geopolymer mortar using a binder from high calcium fly ash. Sodium metasilicate (SM) and sodium hydroxide (SH) were used as solid alkali activators at ratios of 1:1 and 1:2. This study focused on the effect of the dosage and the solid ratio of the alkali activator from SM and SH for the potential to produce a one-part geopolymer. The compressive strength and corrosion resistance of mortar due to sulfuric acid and hydrochloric acid were investigated. The results showed that using a high amount of sodium metasilicate and sodium hydroxide could enhance the development of compressive strength. The fly ash-based one-part geopolymer using sodium metasilicate and sodium hydroxide (SM: NH) at a ratio of 1:1 at 18% achieved the highest compressive strength of 13.3 MPa at 60 days. For the acid attack, it was found that the fly ash-based one-part geopolymer mortar using SM: NH at a ratio of 1:1 had a lower weight change than a ratio of 1:2 after immersion in sulfuric acid. Meanwhile, the fly ash-based one-part geopolymer mortar with SM: NH at a ratio of 1:2 showed higher resistance to hydrochloric acid than at a ratio of 1:1.